Prevalence and clinical course of postoperative acute lung injury after esophagectomy for esophageal cancer - Choi, Hayoung; Cho, Jong Ho; Kim, Hong Kwan; Choi, Yong Soo; Kim, Jhingook; Zo, Jae Ill; Shim, Young Mog; Jeon, Kyeongman (Journal of Thoracic Disease; Vol 11, No 1 (January 26, 2019): Journal of Thoracic Disease, 2019)
Background: Although acute lung injury (ALI) that develops after esophagectomy is associated with significant morbidity and mortality, there is limited information on its overall clinical course. The objective of this study was to investigate the prevalence and clinical course of ALI after esophagectomy. Methods: Data were collected from all consecutive patients diagnosed with ALI after esophagectomy for esophageal cancer from January 2012 through March 2017 and retrospectively analyzed. Results: During the study period, a total of 1,132 patients underwent esophagectomy for esophageal cancer and 52 (4.6%) patients developed postoperative ALI. At the time of ALI diagnosis, the median lung injury score of all patients was 1.8 (1.0–2.0). Among the patients with ALI, 17 (33%) patients required mechanical ventilation (MV) support, of which two failed to wean from MV and 15 were weaned from MV. The median MV duration was 4 days (interquartile range, 3–8 days). Corticosteroids were used in 33 (63%) patients. During corticosteroid treatment, superimposed infections were observed in 10 (30%) patients and surgical site complications were observed in 9 (27%). Overall in-hospital mortality was 10%. Conclusions: The prevalence and mortality of ALI following esophagectomy in our study were lower than those of previous reports. However, the use of corticosteroids in patients with ALI following esophagectomy requires attention to the occurrence of surgical site complications and close surveillance to identify new infections.